1980
DOI: 10.1021/jm00179a007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of phenylethanolamine N-methyltransferase and epinephrine biosynthesis. 1. Chloro-Substituted 1,2,3,4-tetrahydroisoquinolines

Abstract: In a search for inhibitors of epinephrine biosynthesis as potential therapeutic agents, a series of 13 ring-chlorinated 1,2,3,4-tetrahydroisoquinolines was prepared. These compounds were tested initially for their ability to inhibit rabbit adrenal phenylethanolamine N-methyltransferase (PNMT) in vitro. Enzyme-inhibitor dissociation constants, determined for the six most potent members of the series, indicated the following order of decreasing potency: 7,8-Cl2 greater than 6,7,8-Cl3 greater than 7-Cl approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…On the basis of our in vitro BBB model studies, which indicated that 8 would not be able to penetrate the CNS, we decided not to pursue the synthesis of the enantiomers of 8. R-or S-3-Hydroxymethyl-7-bromo-THIQ (14) was synthesized using the conditions outlined in Scheme 2. Hydrogenation of the 7-nitro substituent of R-or S-21 to the amine followed by a Sandmeyer bromination formed R-or S-22.…”
Section: Chemistrymentioning
confidence: 99%
“…On the basis of our in vitro BBB model studies, which indicated that 8 would not be able to penetrate the CNS, we decided not to pursue the synthesis of the enantiomers of 8. R-or S-3-Hydroxymethyl-7-bromo-THIQ (14) was synthesized using the conditions outlined in Scheme 2. Hydrogenation of the 7-nitro substituent of R-or S-21 to the amine followed by a Sandmeyer bromination formed R-or S-22.…”
Section: Chemistrymentioning
confidence: 99%
“…Previous studies have shown that constraining the methylamine side chain of benzylamine (15) to form THIQ (5) increases its hPNMT inhibitory potency 29-fold. 16 Because 18 was found to be more potent and selective for hPNMT than 15, we predicted that constraining the side chain of 18 into a 4,5,6,7-tetrahydrothieno[3,2-c]pyridine (THTP, 14) ring system would likely result in superior hPNMT inhibitory potency and selectivity versus 5.…”
Section: Introductionmentioning
confidence: 99%
“…Because the THIQ nucleus can be viewed as either a constrained benzylamine or a constrained 2-phenylethyl-amine and a common isosteric replacement for a benzene ring is a thiophene ring, the commercially available thiophene analogs of benzylamine (15) and 2-phenylethylamine (16) were evaluated at hPNMT and the α 2 -adrenoceptor ( Table 2). As expected, 2-(2-thienyl)ethylamine (19) was found to have hPNMT inhibitory potency that was similar to phenylethylamine 16.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these 4-fluoro-THBAs (12)(13)(14) were found to be more selective than similarly substituted 3-fluoromethyl-THIQs with the exception of nitrile 15. 4-FluoroTHBAs containing hydrophilic electron-withdrawing 8-substituents (13 and 15) were found to be selective inhibitors of PNMT as anticipated.…”
Section: Discussionmentioning
confidence: 98%